Robust calling performance in frogs infected by a deadly fungal pathogen - Greenspan, Sasha E. (Ecol Evol, 2016)
Reproduction is an energetically costly behavior for many organisms, including species with mating systems in which males call to attract females. In these species, calling males can often attract more females by displaying more often, with higher intensity, or at certain frequencies. Male frogs attract females almost exclusively by calling, and we know little about how pathogens, including the globally devastating fungus, Batrachochytrium dendrobatidis, influence calling effort and call traits. A previous study demonstrated that the nightly probability of calling by male treefrogs, Litoria rheocola, is elevated when they are in good body condition and are infected by B. dendrobatidis. This suggests that infections may cause males to increase their present investment in mate attraction to compensate for potential decreases in future reproduction. However, if infection by B. dendrobatidis decreases the attractiveness of their calls, infected males might experience decreased reproductive success despite increases in calling effort. We examined whether calls emitted by L. rheocola infected by B. dendrobatidis differed from those of uninfected individuals in duration, pulse rate, dominant frequency, call rate, or intercall interval, the attributes commonly linked to mate choice. We found no effects of fungal infection status or infection intensity on any call attribute. Our results indicate that infected males produce calls similar in all the qualities we measured to those of uninfected males. It is therefore likely that the calls of infected and uninfected males should be equally attractive to females. The increased nightly probability of calling previously demonstrated for infected males in good condition may therefore lead to greater reproductive success than that of uninfected males. This could reduce the effectiveness of natural selection for resistance to infection, but could increase the effectiveness of selection for infection tolerance, the ability to limit the harm caused by infection, such as reductions in body condition.